Development of Arabic Language Teaching Materials with a Communicative Approach in the Language Dormitory of the Salafiyah Islamic Boarding School, Syafi'iyah, Sukerejo Situbondo - Maghviroh, Nazilatil (At-Turost : Journal of Islamic Studies, 2019)
The function of language Arabic as languages communication. And the proces of languages teaching nennds elements of support, incluiding teaching contens, because it is a medium that contains a variety of knowledge that must be mastered by student, therefore auther chosee the title Development of Arabic Contens Based on Communicative Aproach. This study used to find out how the process of Development of Arabic Contens Based on Communicative Aproach in Language Boarding school of Salafiyah Syafi’iyah Sukorejo Situbondo. The result of this study is from of product Arabic Language contens and exercies based on Communicative Aproach that can be received by students in Language Boarding school of Salafiyah Syafi’iyah Sukorejo Situbondo and they has a good respon for it because the majority of student (4,97 %)agreed that the contens and exercises that developed cans motivate and help them to communicate with the Arabic Language both speaking and writing.